Optimalisasi Kuat Tekan dan Kuat Lentur Beton Menggunakan Campuran Lateks - Ary Prastowo; Ahmad Ridwan; Edy Gardjito; Zendy Bima Mahardana (Faculty of Engineering, Kadiri University, 2021)
Concrete is a building construction material that has an important role. Concrete itself tends to have strong properties in resisting compressive forces, but weak in resisting tensile or flexural forces. The use of additives in concrete is an option to improve the basic properties of concrete. Latex or rubber latex is one of the natural materials that can be used in concrete mixtures. Its adhesive properties can be utilized in improving the quality of concrete. This study aims to determine the compressive strength and flexural strength of concrete with the addition of latex. The research was conducted experimentally by making concrete specimens in the laboratory. The addition of latex by 10% and 30% with a planned concrete quality of fc' 29.5 MPa. The test object used is a cylinder measuring 15x30 cm and a beam measuring 15x15x30 cm. The tests carried out were testing the compressive strength and flexural strength at the age of 28 days. The results showed that the highest compressive strength was at the addition of 10% latex with a value of 9.96 MPa. While the highest flexural strength value obtained was 3.20 Mpa at the addition of 10% Latex or. From these results it can be seen that the addition of latex has not been able to improve the quality of concrete and has not been able to increase the compressive strength or flexural strength of concrete. So that these results can be used as research development or concrete production.